1996
DOI: 10.1021/es9507170
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Assessment of the Occurrence and Possible Sources of MTBE in Groundwater in the United States, 1993−1994

Abstract: The 1990 Clean Air Act Amendments require fuel oxygenates to be added to gasoline used in some metropolitan areas to reduce atmospheric concentrations of carbon monoxide or ozone. Methyl tert-butyl ether (MTBE) is the most commonly used fuel oxygenate and is a relatively new gasoline additive. Nevertheless, out of 60 volatile organic chemicals analyzed, MTBE was the second most frequently detected chemical in samples of shallow ambient groundwater from urban areas that were collected during 1993−1994 as part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
237
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 378 publications
(241 citation statements)
references
References 25 publications
2
237
1
1
Order By: Relevance
“…Methyl hydroperoxide, CH 3 OOH, has been the subject of numerous publications [20][21][22][23][24] since a comprehensive review by Dorofeeva et al in 2001. 25 They concluded that ∆H f (298.15K) ) -139.0 ( 5.0 kJ mol -1 represented the best estimate from values which ranged from -122 to -143 kJ mol -1 .…”
Section: Alkyl Hydroperoxidesmentioning
confidence: 99%
“…Methyl hydroperoxide, CH 3 OOH, has been the subject of numerous publications [20][21][22][23][24] since a comprehensive review by Dorofeeva et al in 2001. 25 They concluded that ∆H f (298.15K) ) -139.0 ( 5.0 kJ mol -1 represented the best estimate from values which ranged from -122 to -143 kJ mol -1 .…”
Section: Alkyl Hydroperoxidesmentioning
confidence: 99%
“…Volume Two (Squillace et al, 1996). The results show that, of the 60 volatile organic compounds (VOCs) analyzed, MTBE was the second most frequently detected compound.…”
Section: Journal Of Hazardous Substance Research 4-2mentioning
confidence: 99%
“…The high solubility of MTBE in water, combined with its high concentration in some gasoline, can result in high concentrations of MTBE in surface water, ground water and storm water. 2,3 Currently, the most common method for the determination of MTBE is purge-and-trap preconcentration, followed by GC analysis. Purge-and-trap/GC instrumentation is expensive, technically sophisticated and time-consuming to operate.…”
Section: Introductionmentioning
confidence: 99%